Research on 5G private networking schemes for industry - Shilei DONG; Jingbo ZHAO (Dianxin kexue)
5G network with large bandwidth, and the advantages of wide coverage, low latency, the interpersonal communication, extended to the communication between the people and things, things and objects, open everything connected age, but as a result of network planning and design and safety, management and other reasons, the existing 5G network does not apply to 2C industry enterprises.Therefore, the major operators are striving to build 5G 2B private network.In particular, enabling 5G to traditional industries can promote the intelligence, digitization and networking of traditional industries, and effectively improve production efficiency and quality.Based on the research of 5G key technology, combined with the actual industrial scene of a domestic factory, the solution of deep integration of 5G private network and traditional industrial manufacturing field was explored, so as to realize the intelligent transformation of the factory.